2014
DOI: 10.1111/ejh.12426
|View full text |Cite
|
Sign up to set email alerts
|

Primary antifungal prophylaxis with micafungin in patients with haematological malignancies: real‐life data from a retrospective single‐centre observational study

Abstract: Mould-active antifungal prophylaxis is increasingly used in patients at risk for invasive fungal disease. Between June 2011 and June 2012, one hundred patients with various haematological malignancies at risk for invasive fungal disease received primary antifungal prophylaxis with intravenous micafungin at a daily dosage of 50 mg during neutropenia. The median number of days on micafungin prophylaxis was 14 (range, 6-48 d). The incidence of proven and probable breakthrough invasive fungal diseases (bIFDs) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
4
26
1
1
Order By: Relevance
“…The dose of micafungin was chosen based on initial studies suggesting the need for higher doses of anti-mold prophylaxis compared to the dose needed for Candida. 20,21 It is possible that a lower dose of micafungin could be equally effective based on recent data showing effective anti-mold prophylaxis with a daily dose of 50-100 mg. 22,23 Mortality after IMI was high in our patients, consistent with prior reports, 8,24 especially for those with Mucorales, reflecting the aggressiveness of these infections even in the prophylactic era and indicating the need for continuing improvement in this field despite the low prevalence of IMI.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The dose of micafungin was chosen based on initial studies suggesting the need for higher doses of anti-mold prophylaxis compared to the dose needed for Candida. 20,21 It is possible that a lower dose of micafungin could be equally effective based on recent data showing effective anti-mold prophylaxis with a daily dose of 50-100 mg. 22,23 Mortality after IMI was high in our patients, consistent with prior reports, 8,24 especially for those with Mucorales, reflecting the aggressiveness of these infections even in the prophylactic era and indicating the need for continuing improvement in this field despite the low prevalence of IMI.…”
Section: Discussionsupporting
confidence: 89%
“…The dose of micafungin was chosen based on initial studies suggesting the need for higher doses of anti‐mold prophylaxis compared to the dose needed for Candida . It is possible that a lower dose of micafungin could be equally effective based on recent data showing effective anti‐mold prophylaxis with a daily dose of 50‐100 mg …”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, at the present time, most patients with hematological malignancies or cancers undergoing chemotherapy take fluconazole for antifungal prophylaxis (9). In addition, an increasing number of clinical trials have reported to have optimized "prophylaxis" for invasive fungal infections (11). Thus, we demonstrated that afebrile Candida infection can be the sole initial manifestation of systemic disorders including hematological malignancies.…”
Section: Discussionmentioning
confidence: 65%
“…The most popular PAP studies are about the choice of PAP drugs, including retrospective and prospective studies . Triazoles were the earliest and most widely used, accounting for more than 90% of PAP drugs .…”
Section: Discussionmentioning
confidence: 99%
“…The most popular PAP studies are about the choice of PAP drugs, including retrospective and prospective studies. [30][31][32][33][34][35][36] Triazoles were the earliest and most widely used, accounting for more than 90% of PAP drugs. 21 In this study, triazoles were also the most popular PAP drugs (n = 568, 75.8%), 2 followed by echinocandins (n = 98, 13.1%) and AmB (n = 83, 11.1%).…”
Section: Pap In Haematological Patientsmentioning
confidence: 99%